Electron Impact Single Ionization of Al+, Cd+ and Hg+ (Bulletin of Pure and Applied Sciences – Physics, 2020)
Electron Impact single ionization cross sections of Al+ , Cd+ and Hg+ ions have been  calculated in the Modified Binary Encounter Approximation. Accurate expression of  ∆ (cross section for energy transfer ∆E) and Hatree-Fock velocity distributions for  the target electrons have been used throughout the calculations. For positive ions the  focusing effects of the target ion on the incident electron have been incorporated in the calculations. The present results of single ionization cross sections are in  excellent agreement with the experimental observations in the intermediate energy  range. The calculated cross sections differs from the experimental results in the low  energy regions because the present approximation not exhibit better result in the low  energy regions, while the over-estimations of experimental results in the high energy  regions shows that more theoretical calculations is required to understand the  dynamics of the system.